Dominant PAX2 mutations may cause steroid resistant neprotic syndrome and FSGS in children - Vivante, Asaf (Pediatr Nephrol, 2019)
BACKGROUND: Heterozygous PAX2 mutations cause renal coloboma syndrome (RCS) [OMIM# # 120330]. RCS is a renal syndromic disease encompassing retinal coloboma and sensorineural hearing loss. Recently a causative role for PAX2 was reported in adult-onset nephrotic syndrome secondary to focal segmental glomerulosclerosis (FSGS). However, the prevalence of PAX2 mutations among large cohort of children with steroid resistant nephrotic syndrome (SRNS) and FSGS have not been systematically studied. METHODS: We employed whole exome sequencing (WES) to reveal the percentage of SRNS cases explained by monogenic mutations in known genes of SRNS/FSGS. As PAX2 mutations are not an established cause of childhood FSGS we have evaluated a cohort of 215 unrelated families with SRNS, in whom no underlying genetic etiology had been previously established. RESULTS: Using WES, we identified 3 novel causative heterozygous PAX2 mutations in 3 out of the 215 families studied (1.3%). All 3 cases were detected in families with more than one affected and compatible with an autosomal dominant mode of inheritance (3/57 familial cases (5.2%)). The clinical diagnosis in three out of four pediatric index patients was done incidentally during routine medical evaluation. CONCLUSIONS: Our findings demonstrate high frequency of PAX2 mutations in familial form of SRNS (5.2%) and further expand the phenotypic spectrum of PAX2 heterozygous mutations to include autosomal dominant childhood-onset FSGS. These results highlight the importance of including PAX2 in the list of genes known to cause FSGS in children.